A rat CD4 mutant containing the gp120-binding site mediates human immunodeficiency virus type 1 infection. - Simon, J; Somoza, C; Schockmel, G; Collin, M; Davis, S; Williams, A; James, W (1993)
CD4 is the primary receptor for the human immunodeficiency virus type 1 (HIV-1). Early mutational studies implicated a number of residues of CD4, centered in the region 41-59, in binding to gp120. However, further mutational analyses, together with studies using inhibitory antibodies or CD4-derived peptides, have suggested that other regions of CD4 are also involved in binding or postbinding events during infection. To resolve these ambiguities, we used rat CD4 mutants in which particular regions were replaced with the corresponding sequence of human CD4. We have previously shown that some of these are able to bind HIV-1 gp120, and here we test their ability to act as functional receptors. We find that the presence of human CD4 residues 33-62 is enough to confer efficient receptor function to rat CD4, and we conclude that it is unlikely that regions of CD4 outside this sequence are involved in specific interactions with HIV-1 during either infection or syncytium formation.